Fluorescence immunosensor based on functional nanomaterials and its application in tumor biomarker detection. Issue 48 (1st November 2022) - Huang, Juanjuan; Wei, Fenghuang; Cui, Yuling; Hou, Li; Lin, Tianran
Abstract : Fluorescence immunosensors constructed from functional nanomaterials for the detection of tumor biomarkers such as enzymes, RNA, DNA, proteins and cancer cells were summarized. Abstract : An immunosensor is defined as an analytical device that detects the binding of an antigen to its specific antibody by coupling an immunochemical reaction to the surface of a device called a transducer. Fluorescence immunosensing is one of the most promising immunoassays at present, and has the advantages of simple operation, fast response and high stability. A traditional fluorescence immunosensor often uses an enzyme-labelled antibody as a recognition unit and an organic dye as a fluorescence probe, so it is easily affected by environmental factors with low sensitivity. Nanomaterials have unique photostability, catalytic properties and biocompatibility, which open up a new path for the construction of stable and sensitive fluorescence immunosensors. This paper briefly introduces different kinds of immunosensors and the role of nanomaterials in the construction of immunosensors. The significance of fluorescent immunosensors constructed from functional nanomaterials to detect tumor biomarkers was analyzed, and the strategies to further improve the performance of fluorescent immunosensors and their future development trend were summarized.